The Potential Roles of Very Low Calorie, Very Low Calorie Ketogenic Diets and Very Low Carbohydrate Diets on the Gut Microbiota Composition - Rondanelli, Mariangela; Gasparri, Clara; Peroni, Gabriella; Faliva, Milena Anna; Naso, Maurizio; Perna, Simone; Bazire, Philip; Sajoux, Ignacio; Maugeri, Roberto; Rigon, Chiara (Frontiers in Endocrinology, 2021)
Several studies have described a strong correlation between diet, weight loss, and gut microbiota composition. The aim of this review was to evaluate the potential effects of energy-restricted diets, namely very low calorie diets (VLCDs), very low calorie ketogenic diets (VLCKDs), and very low carbohydrate diets (VLCarbDs), on the composition of the gut microbiota in humans. We performed a literature search using the following terms (with their abbreviations or acronyms): “very low calorie diet”, “very low calorie ketogenic diet”, “very low carbohydrate diet”, and “gut microbiota”. Our search strategy retrieved nine eligible studies. Overall, VLCDs and VLCarbDs affected the Bacteroidetes to Firmicutes ratio in obese patients, leading to a reduction in short-chain fatty acid production by fecal microbiota associated with Clostridial cluster XIVa. This reduction particularly affected Roseburia and Eubacterium rectale, the two most abundant butyrate-producing bacteria in human feces. VLCKDs preserved the core fecal microbiome, but altered the composition of fecal microbial populations in relation to the plasma metabolome and fecal bile acid composition. In particular, VLCKD-induced weight loss resulted in a reduction in E. rectale and Roseburia, an increase in Christensenellaceae and Akkermansia while not all studies show a decrease in Faecalibacterium prausnitzii. Although very few studies have analyzed the effects of VLCarbDs and VLCDs on gut microbiota, significant diet-induced changes in fecal microbiota composition have been observed. Further studies are needed.